Extra-skeletal Ewing’s sarcoma with EWSR1::ERG translocation of the breast: a case report - Weiping Li; Yingjun Wu; Xingmei Dong; Xinmin Qiu; Guangjuan Zheng; Yu Zhang (Diagnostic Pathology)
Abstract Background Ewing’s sarcoma (ES), first described by Ewing in 1921, is a highly malignant small blue round cell tumor that arises in bone or extraskeletal soft tissues. It predominantly affects patients aged 10 to 30 years. Approximately 12% of cases involve solid organs, often presenting as rapidly growing masses in deep soft tissues. The most common genetic alteration in ES is the t(11;22)(q24;q12) translocation, resulting in the EWSR1::FLI1 fusion gene, which accounts for 90% of tumors. Extraskeletal Ewing’s sarcoma (EES) presented as a breast mass is extremely rare, with only a handful of cases documented in the literature. Notably, a primary breast ES harboring the EWSR1::ERG fusion gene has never been reported previously. Case presentation A 23-year-old woman presented to our hospital with a rapidly growing, palpable left breast mass. Histopathological examination of the surgical specimens (including histological features, immunohistochemical staining, and molecular analysis) confirmed the diagnosis of primary EES with EWSR1::ERG translocation in the breast. Despite receiving multimodal adjuvant therapy (surgery, chemotherapy and radiotherapy), the patient experienced two disease relapses within 15 months. Conclusions Our report establishes the first molecularly confirmed case of ES harboring the rare EWSR1::ERG translocation presenting as a primary breast mass. Primary breast ES can demonstrate significant morphologic and immunohistochemical overlap with other small round cell tumors. This case highlights that next-generation sequencing (NGS) is the gold standard for definitive diagnosis, as it reliably detects fusion partners-especially in rare tumors arising in uncommon locations.